2006
DOI: 10.1007/s10546-005-5747-7
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Over Urban-type Roughness: Deductions from Wind-tunnel Measurements

Abstract: Turbulence data from experiments conducted over a staggered cube array, modelling a neutrally stable atmospheric boundary layer in an urban environment, are presented. The results support the contention that organised eddy structures in the near-wall region differ significantly from those in regular smooth-wall flows or in rough-wall boundary layers with much smaller h/δ ratios (where δ and h are the boundary-layer thickness and the height of the roughness elements, respectively). Attention is concentrated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
119
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 33 publications
35
119
1
1
Order By: Relevance
“…Our results are consistent with those of Castro et al (2006) who found that spanwise integral length scales obtained from twopoint correlations increased with height. Tomkins and Adrian (2003) also observed a linear scaling of eddy sizes in the corresponding log region over smooth walls, but the eddy sizes there were several times smaller than the present ones.…”
Section: Coherent Structures Above the Buildingssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with those of Castro et al (2006) who found that spanwise integral length scales obtained from twopoint correlations increased with height. Tomkins and Adrian (2003) also observed a linear scaling of eddy sizes in the corresponding log region over smooth walls, but the eddy sizes there were several times smaller than the present ones.…”
Section: Coherent Structures Above the Buildingssupporting
confidence: 93%
“…Moreover, as noted above, the Reynolds number dependence for this type of flow is weak (Xie and Castro, 2006). The adequacy of the grid was confirmed by a close comparison of the statistics with those for a test run at double the resolution but on a smaller domain of 4 h × 4 h × 4 h. Figure 2 demonstrates the good agreement obtained with the wind-tunnel data of Cheng and Castro (2002) and Castro et al (2006). Further comparisons are presented in Coceal et al (2006).…”
Section: Numerical Methods and Geometrysupporting
confidence: 65%
See 2 more Smart Citations
“…A few minor differences are found due to the different building geometry, for example, R u,x falls to 0.2 at δx = 6h and R u,y falls to −0.25 at δy = 2.8h for the flows over an array of staggered 3D cubes. Nevertheless, the LES-calculated R φ,x i behaviours are generally in line with those of the wind-tunnel experiment (Castro et al 2006) and with DNS (Coceal et al 2007). …”
Section: Two-point Correlationssupporting
confidence: 83%